2020
DOI: 10.1021/acsnano.9b09487
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Minimal Heat Conductivity by Ballistic Confinement in Phononic Metalattices

Abstract: Controlling the thermal conductivity of semiconductors is of practical interest in optimizing the performance of thermoelectric and phononic devices. The insertion of inclusions of nanometer size in a semiconductor is an effective means of achieving such control; it has been proposed that the thermal conductivity of silicon could be reduced to 1 W/m/K using this approach and that a minimum in the heat conductivity would be reached for some optimal size of the inclusions. Yet the experimental verification of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 64 publications
1
30
0
Order By: Relevance
“…The demonstration of such control is very important for a fundamental understanding of the design of thermoelectric materials. The correlation between pore size and thermal conductivity in metals and silicon is known; however, electrical conductivity has not been considered. Previous attempts to prepare composites of carbon nanotubes and polymers with low κ values attempted to separately control thermal and electrical conduction; however, the introduction of polymers, which was to reduce κ, significantly decreased σ …”
Section: Introductionmentioning
confidence: 99%
“…The demonstration of such control is very important for a fundamental understanding of the design of thermoelectric materials. The correlation between pore size and thermal conductivity in metals and silicon is known; however, electrical conductivity has not been considered. Previous attempts to prepare composites of carbon nanotubes and polymers with low κ values attempted to separately control thermal and electrical conduction; however, the introduction of polymers, which was to reduce κ, significantly decreased σ …”
Section: Introductionmentioning
confidence: 99%
“…19,20 Using the vapor-phase counterpart of this technique, high-pressure confined chemical vapor deposition (HPcCVD), we are now infiltrating semiconductors into the nanoscale voids of the silica template. 21,22,23 These inverse structures, defined as metalattices, inherit the void structure of the template to form an interconnected periodic lattice.…”
mentioning
confidence: 99%
“…Even with ligand modifications, however, it is challenging to integrate particle interconnectivity, periodicity, and quantum confinement into one system. This problem has motivated other synthetic approaches to 3D interconnected periodic structures at the nanoscale, especially the synthesis of mesoporous structures by hard or soft templating methods. , Recently Liu et al reported an approach to synthesizing completely connected, atomically crystalline three-dimensional metal structures using high-pressure confined chemical fluid deposition and silica nanoparticle colloidal crystal templates. , Using the vapor-phase counterpart of this technique, high-pressure confined chemical vapor deposition (HPcCVD), we are now infiltrating semiconductors into the nanoscale voids of the silica template. ,, These inverse structures, defined as metalattices, inherit the void structure of the template to form an interconnected periodic lattice.…”
mentioning
confidence: 99%
“…Designing semiconductors with desired thermal conductivity (κ) is of great interest for both thermal management applications and thermoelectricity. It is already well established that building nanostructures with multiple length scales that scatter phonons at different wavelengths is an excellent strategy to reduce the lattice contribution to the thermal conductivity. The presence of disorder in alloys is also well known to scatter high-frequency phonons, while superlattices (SLs) take advantage of zone folding and of the acoustic mismatch between the SL components to effectively scatter phonons of medium-to-long wavelengths. In SLs, the crystalline quality, the period, the acoustic mismatch between the layers, the roughness of the interfaces, the chemical mixing at the interfaces, and the total thickness have significant impact on the thermal conductivity .…”
Section: Introductionmentioning
confidence: 99%